Aplicación de penas sustitutivas por circunstancias atenuantes en las contravenciones de tránsito que tienen como sanción la prisión en el Código Orgánico Integral Penal - Díaz Sarango, María Janina (2023)
This research work entitled: "Application of alternative penalties for mitigating circumstances in traffic violations that have prison as a sanction in the Comprehensive Criminal Organic Code", has as its objective, to carry out a doctrinal, legal and social analysis of the need for impose penalties in a proportional and attenuated manner in cases of traffic violations that are punishable by imprisonment and in this way contribute to the reduction of prison overcrowding. The study carried out shows that the application of custodial sentences in cases of traffic offenses is affecting other rights of offenders, such as the right to work, and the right to protection, for which reason it should be impose sanctions that include non-custodial penalties, in accordance with the mitigating circumstances that may arise in the criminal process. In this thesis, materials and methods were applied which allowed the development of the investigation; Interviews and surveys were conducted with legal professionals, specifically in the field of traffic and road safety, results that served to propose the reform projects of the Law to the Comprehensive Organic Criminal Code, allowing non-custodial sentences to be applied, when There are extenuating circumstances, in traffic offenses, for driving a vehicle with tires in poor condition, for driving while intoxicated, or, in first class offenses